GAMBARAN KINERJA TENAGA PELAKSANA ELIMINASI FILARIASIS DALAM PELAKSANAAN POPM FILARIASIS DI KABUPATEN SEMARANG (Studi di Wilayah Kerja Puskesmas Dadapayam) - Anggi Gian Saputra; Lintang Dian Saraswati; Nissa Kusariana (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Filariasis is an infectious diseasexcaused by filarial worms and transmitted through mosquito bites. Semarang District is one of the endemic areas of filariasis and the Mass Drug Administration filariasis program is being implemented from 2017 to 2021. However, it has not yet reached the target results of mass treatment coverage. Research purpose was to identify factors related to the work performance of filariasis elimination personnel in Mass Drug Administration in the work area of Dadapayam Health Center. This was analytical study with cross sectional approach. Proportionate random sampling technique was applied to obtain 155 samples of respondents. The results showed that 53.5% of respondents had high knowledge, 69% had optimal counseling, and 42.6% had a good perception of their work. Proportion of respondents thought that optimal health center staff supervision were 62.6%, availability facilities of respondents were adequate 56.8%, 54.8% of respondents had high motivation when implementing mass treatment, and 41.3% of respondents experienced obstacles when implementing mass treatment. Proportion of respondents with optimal work performance in filariasis mass treatment were 51%, however there were still many activities that had not done optimally. Results of bivariate analysis indicated a significant association between respondents level of knowledge, type of work, status of counseling, supervision of health center, motivation with the performance of elimination personnel by implementation of mass drug administration filariasis in Dadapayam Health Center. There is no significant association between the ages, level of education, perceptions, availability of facilities, obstacles, level of income with the performance of elimination personnel by implementation of mass drug administration filariasis in Dadapayam Health Center.